Come Together: Protein Assemblies, Aggregates and the Sarcostat at the Heart of Cardiac Myocyte Homeostasis - Islam, Moydul; Diwan, Abhinav; Mani, Kartik (Frontiers in Physiology, 2020)
Homeostasis in vertebrate systems is contingent on normal cardiac function. This, in turn, depends on intricate protein-based cellular machinery, both for contractile function, as well as, durability of cardiac myocytes. The cardiac small heat shock protein (csHsp) chaperone system, highlighted by B-crystallin (CRYAB), a small heat shock protein (sHsp) that forms ~3-5% of total cardiac mass, plays critical roles in maintaining proteostatic function via formation of self-assembled multimeric chaperones. In this work, we review these ancient proteins, from the evolutionarily preserved role of homologs in protists, fungi and invertebrate systems, as well as, the role of sHsps and chaperones in maintaining cardiac myocyte structure and function. We propose the concept of the ‘sarcostat’ as a protein quality control mechanism in the sarcomere. The roles of the proteasomal and lysosomal proteostatic network, as well as, the roles of the aggresome, self-assembling protein complexes and protein aggregation are discussed in the context of cardiac myocyte homeostasis. Finally, we will review the potential for targeting the csHsp system as a novel therapeutic approach to prevent and treat cardiomyopathy and heart failure.